Effect of divalent metal ions on the activity and stability of β-galactosidase isolated from Kluyveromyces lactis - Paulo Roberto Adalberto; Antonio Carlos Massabni; Eleonora Cano Carmona; Antônio José Goulart; Daniela Parreira Marques; Rubens Monti (São Paulo State University (UNESP), 2010)
In this study, it was demonstrated that β-galactosidase can be deactivated and reactivated with EDTA and divalent metal ions. The enzyme was deactivated after 20 minutes in EDTA solution. Maximal deactivation at the lowest EDTA concentration (10-3 mol.L-1) occurred in the presence of Tris-HCl buffer (pH 7.0). The enzyme recovered 50% of its initial activity after 10 minutes at Mg2+concentrations higher than 0.1 mmol.L-1. Experimental concentrations of 0.1 mmol.L-1 Mn2+ and 1.0 mmol.L-1 Co2+ were sufficient to reactivate the enzyme to around 300% of the control activity for the Mn2+ ion and nearly 100% for the Co2+ ion. The enzyme gradually lost its activity when the Co2+ concentration was 10-2 mol.L-1. Ni2+ and Zn2+ were unable to restore the catalytic activity. Km app and Vmax app were 1.95 ± 0.05 mmol.L-1 and 5.40 ± 0.86x10-2 mmol.min-1.mg-1, with o-NPG as substrate. Optimal temperature and pH were 34oC and 7.5. The half-life (t1/2) at 30°C was 17.5 min for the holoenzyme and 11.0 min for the apoenzyme. With respect to pH variation, the apoenzyme proved to be more sensitive than the holoenzyme. Keywords: β-galactosidase. Divalent metallic ions. Enzyme activity. Stability. RESUMO Efeito de íons metálicos divalentes na atividade e estabilidade da β-galactosidase isolada de Kluyveromyces lactis Este estudo demonstra como a β-galactosidase pode ser desativada e reativada usando EDTA e íons metálicos divalentes. A enzima foi desativada após 20 minutos na presença de EDTA. Desativação máxima para a menor concentração de EDTA (10-3 mol.L-1) ocorreu na presença do tampão Tris-HCl. A enzima recuperou 50% de sua atividade inicial após 10 minutos na presença de Mg2+ em concentrações superiores a 0,1mmol.L-1. Concentrações de 10-4 e 10-3mol.L-1 de Mn2+ e Co2+ foram suficientes para reativar a enzima em 300% comparado ao controle de íons Mn2+ e aproximadamente 100% para íons Co2+. A enzima perdeu gradualmente a sua atividade quando a concentração foi de 10-2 mol.L-1. Ni2+ e Zn2+ foram incapazes de restabelecer a atividade catalítica. Km app e Vmax app foram 1,95 ± 0,05 mmol.L-1 e 5,40 ± 0,86 x 10-2 mmol.min-1.mg-1. A temperatura e pH ótimos foram 34ºC e 7,5. A meia vida da holoenzima foi de 17,5 min a 30ºC e para a apoenzima foi de 11,0 min a 30ºC. Quanto à variação de pH, a apoenzima provou ser mais sensível que a holoenzima. Palavras-chave: β-galactosidase. Íons metálicos divalentes. Atividade enzimática. Estabilidade.